2018
DOI: 10.1002/adts.201800080
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Dynamical Dissipative Structures in a Bistable Spin Crossover Solid Under Light: Experience and Theory

Abstract: In this article, the basic spatiotemporal theory elucidating the physical conditions leading to the emergence of dissipative structures and pattern formation in spin-crossover solids under light causing their photo-heating is outlined. In this context, the spatiotemporal properties of the spin-crossover (SC) transition are described as a reaction diffusion process. The time evolution of the spin state (the high spin fraction) is coupled to the spatiotemporal properties of temperature inside the lattice, accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…6(a), blue curve]. It is worth noticing that these behaviors are linked to a theoretical predictive work [53], in which we found that self-organized spin-state structures can emerge from the competition between light and temperature in the vicinity of a thermal hysteresis. On the other hand, previous experimental studies [17,54,55] on light-induced self-organization of the spin states, performed by Laue neutron diffraction (on single crystal) and photomagnetic (on powder material) investigations suggested the occurrence of a light-induced phase separation in the LITH regime, but the latter was not imaged.…”
Section: Reverse Light-induced Thermal Hysteresis By Om: Selective Do...mentioning
confidence: 51%
“…6(a), blue curve]. It is worth noticing that these behaviors are linked to a theoretical predictive work [53], in which we found that self-organized spin-state structures can emerge from the competition between light and temperature in the vicinity of a thermal hysteresis. On the other hand, previous experimental studies [17,54,55] on light-induced self-organization of the spin states, performed by Laue neutron diffraction (on single crystal) and photomagnetic (on powder material) investigations suggested the occurrence of a light-induced phase separation in the LITH regime, but the latter was not imaged.…”
Section: Reverse Light-induced Thermal Hysteresis By Om: Selective Do...mentioning
confidence: 51%
“…These models account for the coupling between the spin-state change and the local volume change of the lattice, opening the way to a very realistic description of the SCO problem, in which electronic (spin) and structural (lattice parameter) degrees of freedom are strongly coupled. Later on, reaction–diffusion models, ,,, derived from the spatiotemporal analysis of the mean-field free energy of Ising-type models, also allowed a nice description of the front propagation processes of the HS/LS interfaces at the thermal transition as well as for the photothermal control of the interface motion …”
Section: Introductionmentioning
confidence: 99%